Status Gizi dan Kepatuhan Konsumsi Tablet Fe dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Kecamatan Tebet - Aurelia Alget Berthelin; Laila Ulfa; Atik Kridawati (Politeknik Kesehatan Kartini Bali, 2022)
Anemia in pregnancy is a risk factor for maternal and fetal health. There are various factors that cause this problem to become complex. During pregnancy has been programmed nutritional management of pregnant women. One of the nutrients needed is iron. Giving Fe tablets as an effort to prevent anemia during pregnancy. Problems arise due to the mother's incorrect nutritional intake and non-compliance with the consumption of Fe tablets. The purpose of this study was to analyze the relationship between compliance with Fe tablet consumption and the nutritional status of pregnant women to the incidence of anemia in pregnant women in Tebet Subdistrict Health Center, South Jakarta in 2021. The study used a cross sectional design with a total of 92 respondents, using a simple random sampling method. The results of this study showed that there was an association with nutritional status (p=0.0001;OR= 32,351) and adherence to tablet consumption plus Fe (p=0.001; OR=5,870) with the incidence of anemia. Pregnant women whose nutritional status is at risk have 32 times greater for anemia, while pregnant women who do not obediently take Fe tablets are at risk 5.87 times greater for anemia. The conclusion of this study is that nutritional status that is at risk and not improved can increase the risk of anemia in pregnant women. Advice for pregnant women to eat more diverse foods to increase iron absorption and obediently consume Fe tablets and do not consume iron absorbance inhibitor foods during pregnancy.